BASIS OF ISLAMIC COUNSELING IN THE PERSPECTIVE OF QURAN VERSES ON GUIDANCE AND COUNSELING - sufian Suri; Irwanto Irwanto (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2021)
This paper aims to describe the basic counseling guidance contained in the Qur'an. The benefits of which lead to efforts in providing assistance given by a counselor to someone in order to optimally overcome the problem. This situation was developed directly by the Prophet Muhammad. In the spiritual value given by the Rasulullah, that Allah SWT provides guidance for individuals who are looking for guidance as guidance, then this step is followed by his friends such as Umar and Usman, Counseling guidance at this time is given as an Islamic counseling service carried out with several services, such as: al-tabayyun, al-hikmah, al-mau'idhah, and also al-mujlah. This study is in the form of library research, using descriptive qualitative methods, with a hermeneutic content analysis approach. The word counseling in Arabic is al-Irshad, which also means al-Huda, ad-Dalalah, meaning guidance. Referring to the value of the Quran on counseling leads to the formation of Muslim personalities in the aspects of aqidah and monotheism as well as in the aspects of sharia and morals.